Analysis of the development of lexical stock in the context of synonymous words in English - BALTAYEVA NODIRA TIMUROVNA; BALTAYEV MEYRXAN BATIROVICH (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article is about the development of a dictionary reserve during a comparative analysis of synonym words in English language, synonyms are words whose pronunciation, writing are different, the meaning of which is different from each other by a number of features, such as the subtleties of additional meanings, the application of emotional meaning, the meaning of which is identical. The present tense imposes a number of tasks on linguists and teachers in the theoretical and practical study of synonyms in English. And this requires the consideration of some measures of on signalization of the process of teaching English, establishing colloquial relations. It consists in creating an understanding of the use of synonyms in English by students and students.